The Use of Gaseous Ozone to Reduce the Microbial Load of Rhubarb (Rheum L.) Petioles as an Additive to Craft Wheat Beers - Zardzewiały Miłosz; Belcar Justyna; Gorzelany Józef (Acta Universitatis Cibiniensis. Series E: Food Technology, 2023)
Rhubarb (Rheum rhaponticum L.) is a valuable source of active components responsible for laxative, antibacterial, diuretic, anti-inflammatory and anti-cancer properties. On the other hand, ozone being an allotropic form of oxygen, due to its potential is a powerful antimicrobial agent. Treatment of rhubarb petioles with gaseous ozone, especially at a concentration of 50 ppm, for 30 minutes had a positive result on the microbiological stability and quality of the finished material. Sensory evaluation of prepared beers enriched without ozonated and ozonated rhubarb pulp showed that wheat beer with the addition of ozonated (50 ppm) rhubarb pulp was characterized by a balanced aroma and taste. The physico-chemical analysis of wheat beers demonstrated that the increasing concentration of ozone had an impact on, among others, increased the degree of final real attenuation (by 21.97%), decreased pH (by 18.43%) and energy value (by 36.30%), but had a negative impact on the content of ethyl alcohol (by 17.32%) compared to the control beer. Among the analyzed beers enriched with rhubarb, the beer product with the addition of ozonated (50 ppm) rhubarb was the most microbiologically stable. The research shows that wheat beers enriched with fragmented rhubarb can be a new trend to expand the range of wheat beers, and the use of gaseous ozone, especially at a concentration of 50 ppm for 30 minutes, can be a trend to extend the microbiological stability of beers, especially craft beers.